Infångning av koldioxid från kemcyklisk förbränning med hjälp av Benfield-processen - Ehlmé, Elias; Ceder, Jakob (My University, 2020)
The Benfield process is a process that captures carbon dioxide by chemical absorption and desorption with a solvent containing potassium carbonate and water. The process is interesting from an environmental perspective since the solvent that is both non toxic and accessible can capture carbon dioxide which then can be stored ​geologically. It’s especially interesting in the case of combustion with biomass. This is because the plants before they are used as fuel have collected carbon dioxide from the atmosphere which after combustion is captured and stored resulting in a net negative carbon dioxide emission. The purpose of this paper was to quantify the energy need for the Benfield process and determine the impact of the inflow gas to the process. This can be accomplished by implementing chemical looping combustion. As a reference point the work data from Stockholm Exergi was used. Stockholm Exergi have previous experience with the Benfield process and plan on adding the process to their largest combined heat and power plant that uses biomass in traditional combustion with air. In this work a number of gases entering the Benfield process with different carbon dioxide concentrations were studied with the help of a calculation model that was built within the framework of the investigation. The results from the theoretical calculations show that the combined sellable energy products, heat and electricity, where rather unaffected after the installation of the Benfield process. Nevertheless, the amount of sellable electricity will drastically be decreased with between 55 to 70 percent of the total electricity produced from the combined heat and power production This could be acceptable in regions where the price for heat and electricity are of the same order, because the electricity consumed in the process can be recovered as heat. However for a power plant that produces soly electricity the reduction in power production will be in the order of 37 to 48 percent, which makes the Benfield process rather uninteresting for this case. The results from the work shows that the energy need is decreasing for an increase of the carbon dioxide concentration in the entering gas and at the same time the total amount that is captured also increases. This shows that if a plant is thinking about installing a Benfield process they should also look at the possibility of increasing the carbon dioxide for the gas entering the process. This is something chemical looping combustion could potentially make possible. Thought about how chemical looping combustion could be implemented is presented in the work.
Keywords: Benfield-process; carbon capture; chemical looping combustion; carbon dioxide; potassium carbonate